Tratamento de água residuária de fecularia e produção de biogás em reator anaeróbio de leito fixo e fluxo contínuo - Araujo, Izabela Regina Costa (2015)
Researches have shown that among several ways of treating cassava starch wastewater, anaerobic process has been considered a simple and economical option that combines the high content of organic matter conversion to biogas production. On the other hand, biogas is a potential energy resource that can be used to supply part of the energy demands from industrial plants. Thus, this trial aimed at evaluating an anaerobic reactor with fixed bed up-flow, regarding the removal of organic load in wastewater from cassava starch extraction as well as biogas production. So, volumetric organic loads (VOC) of 2.5; 5.0; 8.0 and 10.0 g.L-1.d-1 were tested in a 2.82 L volume reactor. A support medium of polypropylene rings filled with polyurethane foam was used. The monitored parameters regarding the reactor effluent were: pH, volatile acidity (VA), total alkalinity (TA), VA/TA ratio, total solid concentrations (TS), volatile solids (VS), total suspended solids (TSS), volatile suspended solids (VSS), total chemical oxygen demand (TCOD), soluble chemical oxygen demand (SCOD) and organic acids. The reactor performance was tested in relation to removals of solids, organic load, as well as biogas and methane production. As the most important results, it was observed that the reactor remained constant concerning pH, total removal of VSS and removals of TCOD and SCOD. While, there were also lactic, butyric, propionic and acetic acids in the studied effluent, although acetic acid was recorded in higher concentrations. Biogas production average was 3.8 L.d-1, the average of specific biogas production was 0.156 L.gCODconsumed-1, but VOC answer was 10.0 g.L-1.d-1, being the greatest results for both of them. Methane percentage in biogas ranged from 66 to 84% and the specific methane production ranged from 0.01 to 0.36 Lg-1. The highest values were obtained in VOC - 2.5 and 10.0 g.L-1d-1, respectively. The removal of medium TS, VS, TSS and VSS were 72, 80, 63 and 92%, respectively. The average removals of TCOD and SCOD were 98.7 and 97.9 respectively, therefore, the highest removal rates were obtained for 10.0 and 2.5 VOC g.L-1.d-1. Thus, it can be concluded from this trial that it is possible to produce biogas with a methane percentage higher than 80% (maximum) and remove the organic loading rate by more than 90% (maximum) according to tested configuration systems with wastewater from cassava starch industry. Furthermore, the highest biogas productions were obtained for the highest VOC, while it was observed a bias on biogas production with VOC increase as well as the specific production of methane.